네트워크 미디어 유튜브에 나타난 서울중심 언론의 지역 언론 콘텐츠 전재: TV매일신문의 원희룡부인 인터뷰 사례 분석 - 박한우(Han Woo Park); 윤호영(Ho Young Yoon) (한국콘텐츠학회 논문지, 22(6), 2022)
This study explores that how the logic of network power in the existing digital content distribution structure works against local media. The limitless citation of local media content, in particular, is becoming more common in order to profit from network traffic while not giving appropriate remuneration for local media content. This study tried to demonstrate how network media dominance alienates local media material by using YouTube network analysis of TV Maile Shinmun. According to the research result, it was found that major news media tends to take profits from the local media interview by not properly indicating the source video, or reporting the core content of the local media interview, making it unnecessary to look for the original video source. Despite the viewpoint that the digital environment presents opportunities for local media, the current network logic would not benefit local media, which calls for the need that the digital content distribution strategy of local media develops a new order such as NFT, one of blockchain-based monetary system.h the help of information technology. 본 연구는 디지털 환경이 지역 언론의 기회라 보는 견해에도 불구하고, 기존의 디지털 콘텐츠 유통 구조에서 행사되는 네트워크 권력 논리가 지역 언론에게 어떻게 불리하게 작용하는지 살펴보는 연구이다. 보다 구체적으로, 지역 언론의 콘텐츠를 인용하여 네트워크 트래픽을 가져가서 수익을 올리고 지역 언론의 콘텐츠는 정작 정당한 보상을 받지 못하는 일이 빈번해지고 있는 사례를 분석했다. TV매일 신문의 원희룡 지사 부인 인터뷰에 대한 유튜브 네트워크 분석을 통해 보여줌으로써, 네트워크 미디어 권력이 지역 언론의 콘텐츠를 어떻게 소외시키는지 보여주고자 하였다. 연구 결과에 따르면, 인터뷰 영상을 인용하는 형식을 띄면서도 원본 출처를 언급하지 않거나, 실상 핵심적 내용을 보도하여 원본 영상을 찾아볼 필요가 없게 만들면서 유튜브 시청 수익을 가져가는 형태가 나타남을 알 수 있었다. 본 연구는 지역 언론의 디지털 콘텐츠 유통 전략이 기존의 네트워크 미디어 질서에서 NFT와 같은 새로운 질서를 구축할 필요성이 있음을 제기하고 있다.